Beyond Medicine: Transforming Healthcare for a Sustainable Future - Souza, Keerthi D; Labhasetwar, Dr. Nitin; Agarwal, Vijay; Joseph, Lallu (South Eastern European Journal of Public Health, 2024)
Aim:To assess the integration of sustainability principles in the Indian health care sector, by gauging the impact of Environmental, Social and Governance (ESG) factors across the healthcare value chain, and to navigate their way towards a sustainable health care system. Subjects and Methods:A detailed literature review was done first, and different stakeholders were carried out in order to identify key sustainability issues. Data collection focused on ESG elements within hospitals. The study collected data from a range of healthcare professional by taking into consideration hospital size, complexity and organizational strategies. Results: The assessment pointed out the healthcare establishments’ attitude towards sustainability, especially in the Economy & Governance, Environmental and Social domains. The hospitals had advantages, including but not limited to, information security, sustainable procurement strategies, as well as increasing women in managerial positions. At the same time, certain environmental challenges showed efficient waste disposal, possible improvement of carbon footprint management, particularly monitoring of GHG emissions. Social dimension, the hospitals focused on providing safe services to patients and training their personnel adequately, did not engage in child labor, and complied with minimum wage regulations in the country.Conclusion:The research underscores the importance of hospitals going beyond simple institutional commitments to sustainability and adapting practices to manage climate change risks and other environmental issues. The findings are intended to help policymakers adopt a more integrated perspective by promoting the adoption of sustainability in the Indian health system in terms of economic, environmental, and social dimensions.